Painted Leather Shirt - Unknown
Painted sea lion hide armour from the Lord Bossom Collection. Sleeveless with fringe on right side, enclosure with toggles. Painted formline crest on front is either an orca or whale design. Denoted in the abstract depiction of offspring bearing, typical of marine mammals. Possibly of Tsimshian origin.